Reconstitution reveals the functional core of mammalian eIF3 - Masutani, Mamiko (Nature Publishing Group, 2007)
Eukaryotic translation initiation factor (eIF)3 is the largest eIF (∼650 kDa), consisting of 10–13 different polypeptide subunits in mammalian cells. To understand the role of each subunit, we successfully reconstituted a human eIF3 complex consisting of 11 subunits that promoted the recruitment of the 40S ribosomal subunit to mRNA. Strikingly, the eIF3g and eIF3i subunits, which are evolutionarily conserved between human and the yeast Saccharomyces cerevisiae are dispensable for active mammalian eIF3 complex formation. Extensive deletion analyses suggest that three evolutionarily conserved subunits (eIF3a, eIF3b, and eIF3c) and three non-conserved subunits (eIF3e, eIF3f, and eIF3h) comprise the functional core of mammalian eIF3.